Elias and his trees - Rivera, Augie D. Jr.; Rivera, Mike; Forbes, Romeo; Giono, Jean (Quezon City : CANVAS, 2009)
A story of a man looking to rediscover his roots. Growing up, his parents told him of their land of birth - of its green mountains, lush forests, pristine streams, and towering trees. These memories eventually led him back to the Philippines...back to the remote town of Tierra Verde. He did not find the Tierra Verde of his father and mother's childhood. That place was long gone -- cut down...washed away...now barren, abandoned, forgotten. What he found was one solitary man named Elias Dakila, who barely spoke and who had no one else but his dog. Elias Dakila simply planted trees. Their unlikely friendship would span 45 years. Elias Dakila would bring him back home and in the process, create a masterpiece truly worthy of God.
First published in hardcover by UST Publishing House, 2005.
Keywords: Children's stories, Filipino; Electronic Books